Klinický obraz a diagnostika subarachnoidálního krvácení z ruptury aneurysmatu - Krajícková, D (Sbornik vedeckych praci Lekarske fakulty Karlovy univerzity v Hradci Kralove. Supplementum, 1995)
Ruptured cerebral aneurysm is the most common cause of non-traumatic subarachnoid hemorrhage. Subsequent to this catastrophe, patients have usually evidence of severe headache with sudden onset, signs of meningeal irritation, and depression of consciousness. Difficulties in diagnosis arise when the clinical picture is not classical. Cerebral vasospasm following aneurysmal subarachnoid hemorrhage is the leading cause of death and disability after aneurysm rupture. In the presence of a typical history and a normal CT scan, lumbar puncture should be performed with spectrophotometry analysis of the supernatant. After subarachnoid hemorrhage has been confirmed, four-vessel angiography should be performed as soon as possible. The surgical treatment of subarachnoid hemorrhage caused by ruptured aneurysm is the method of choice.
Keywords: Subarachnoid Hemorrhage; subarachnoidální krvácení; Aneurysm, Ruptured; intrakraniální aneurysma; Humans; Intracranial Aneurysm; lidé; prasklé aneurysma